IMPLEMENTATION OF CRIMINAL SANCTIONS FOR VIOLATION OF SELLING IN PROHIBITED PLACES - Joharsah (International Journal of Educational Research Excellence (IJERE), 2022)
Formula problem on study This is factor reason happening violation selling where it is prohibited , obstacles are accepted in the process of completion case Violation selling where prohibited And what to do in application penalty to violation selling in prohibited places. As for who became objective from study ie For knowing the factors that cause violations of selling in prohibited places, knowing the obstacles received in the process of resolving cases of violating selling in prohibited places and knowing what efforts have been made in imposing sanctions on violations of selling in prohibited places. Results study This show Factor reason happening violation selling where it is prohibited is narrow field accompanying adequate work with enhancement amount unemployment , yes difficulty economics , yes opportunity business with little capital And Enough interested many people are affected in a manner economy as well as exists current very urbanization heavy . Obstacles received in the process of completion case Violation selling where prohibited consists from internal factors and factor external . Internal factors include lack of personnel and owned fleet officer. Whereas factor external that is not enough evenly socialization rule trade right , lack location available construction, distribution information And method delivery less information understandable as well as lack of awareness law for street vendors . Attempts made in application penalty to violation selling where prohibited is increase attention government against street vendors through arrangement provision adequate location And worth , improvement activity prevention through patrol officer as well as Enhancement security independently in each environment Good settlement nor vital place . Should government can give solution with provide place selling right And in accordance for street vendors so that existence No bother order general.